Influence of microwave on dissolution medium and its effect on sulfamerazine and sulfathiazole dissolution / Azzakirah Iskhandar - Iskhandar, Azzakirah (2007)
The influence of microwave irradiation on dissolution medium and its effect on dissolution profiles of sulfamerazine and sulfathizole were investigated. The dissolution medium was subjected to microwave irradiation at 80 W for 37.5 min, and 300W for 10 min. The profiles of drug dissolution in these media were compared to the untreated counterpart by drug dissolution testing, drug solubility, media pl-I, temperature, conductivity, UY and FTIR spectroscopy analysis. The irradiation of microwave was found to exert varying effects on the dissolution medium. Generally, the treatment of dissolution medium by microwave at 80 and 300W led to changes in pl-I, conductivity and mobility of water molecules. It appeared that the dissolution medium gained a higher degree of mobility upon its treatment by microwave thus leading to an increase in extent of sulfamerazine and sulfathiazole dissolution.